The Influence of Discovery Learning and Problem Based Learning Models on Citizenship Education Learning Outcomes - Maduwu, Ferinus; Winarno, Winarno; Muchtarom, Moh. (International Journal of Educational Research & Social Sciences, 2024)
This research aims: (1) To determine the effect of the Discovery Learning learning model on student learning outcomes in Class XI Citizenship Education lessons at the Teluk Dalam Campus Private High School. (2) To determine the effect of the Problem Based Learning learning model on student learning outcomes in Class XI Citizenship Education lessons at Teluk Dalam Campus Private High School. (3) To determine the significant differences between the Discovery Learning and Problem Based Learning models on student learning outcomes in Class XI citizenship education at the Teluk Dalam Campus Private High School. The research method uses quantitative methods in the form of experiments. The population in this study were all class XI students at the Teluk Dalam Campus Private High School, and the samples chosen were class The data collection technique is by means of a learning outcomes test in the form of multiple choice questions, the learning outcomes test is carried out twice, namely (1) a pre-test carried out before implementation in the experimental class (discovery learning) and in the control class (problem based learning), (2) the post-test is carried out after implementation in the experimental class (discovery learning) and in the control class (problem based learning). The technical analysis of this research data uses test requirements in the form of normality and homogeneity tests as well as hypothesis testing using the t-test. The results of the research show that there is a significant difference between the pre-test scores and the post-test scores in the experimental class which uses the discovery learning model and in the control class which uses the problem based learning model. This is proven based on the results of the paired sample T-test table, it is known that the pair value is 1 sig. is 0.000 < 0.05 then Ha is accepted and HO is rejected. Furthermore, the research results showed that there was no difference in the learning outcomes of students studying PPKN for class. This is proven by the results of the t-test with a significance level of 0.093 (0.903 > 0.05). This means HO is accepted and H1 is rejected or HO is rejected or H1 is accepted. Based on the results of this research, it can be concluded that there is no significant difference in PPKN learning outcomes for class.